Prevalence of the temporomandibular disorders and most common associated factors presented in the ninth and tenth semester clinics of the Universidad Santo Tomás in the second period of the year 2016 - Suarez, Andres Felipe; Gamarra, Martin Adolfo; Sanchez, Olga Liseth; Morales, Iader Francisco (Revista Estomatología, 2017)
Aim: To establish the prevalence of temporomandibular disorders (TMD) presented by patients who attended the dental clinics of the ninth and tenth semester of the Santo Tomas University in the second period of 2016. Materials and Methods: A cross - sectional, observational, descriptive study was carried out, with a sample of 113 clinical records. The sample was collected from clinical records already completed from the clinics of ninth and tenth semester of the University Santo Tomas in the second period of the 2016. Using descriptive statisticsfor the univariate analysis. In the bivariate analysis, a relationship between TMD and the variables of interest was established using the t-student and Chi-square test, where a value of p≤0.05 was considered statistically significant. Results: Of the 113 clinical records, 131 diagnoses were obtained. The prevalence of one or more TMD was 55.7%, of which 30.1% were women diagnosed with TMD. The most prevalent TTM was the unilateral subluxation in 11.4% of the cases. Of the associated factors, joint noise predominated with 43.4% where the predominant type of noise was the click with 91.8%, followed by muscle pain. Conclusions: The prevalence of TMD was high, represented in 55.7% of the population. The most common TMD was unilateral Subluxation with 11.4%. We found a statistically significant association between at least one sign and symptom type factor, dental factors and one or more TMD.